RANCANG BANGUN SISTEM KONVERSI UANG LOGAM MENJADI E-MONEY BERBASIS MIKROKONTROLER DAN APLIKASI ANDROID - Baskara Puruhita Wija, D M; Raka Agung, I G A P; Rahardjo, Pratolo (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUM, 2021)
Money is a medium that is used as a means of buying/selling. Indonesia uses the Rupiah currency with 2 types of money used, one of which is coins. Coins are generally used in transactions of small amounts, but in some cases, coins are used in transactions of large amounts. This caused problems in counting and sorting coins in terms of time and energy. Through this problem, a coin sorting and the counter system was developed that could be converted into E-Money and integrated with an Android-based smartphone. The system is designed with 2 parts, namely hardware and software. The sorting system is created using the different diameters of each coin. The counting system uses IR Sensor to detect coins and counts on the ESP32. Testing on the system is carried out in 3 stages, namely testing the tool system, testing the Android application system, and testing the whole system. The system for converting coins to e-money is made using the ESP32 as the main microcontroller with Bluetooth as a medium of communication with smartphones. The coin sorting board is made into 4 strips and has holes the same size as the diameter of the coins. In the coin counting system, the tool has been able to count up to 250 coins in 8 minutes 21 seconds with an accuracy percentage above 80%.